Formal Modeling and Analysis of Timed Systems 13th International Conference, FORMATS 2015, Madrid, Spain, September 2-4, 2015, Proceedings - Sankaranarayanan, Sriram; Vicario, Enrico (Theoretical Computer Science and General Issues, 2015)
This book constitutes the refereed proceedings of the 13th International Conference on Formal Modeling and Analysis of Timed Systems, FORMATS 2015, held in Madrid, Spain, in September 2015. The conference was organized under the umbrella of Madrid Meet 2015, a one week event focussing on the areas of formal and quantitative analysis of systems, performance engineering, computer safety, and industrial critical applications. The 19 papers presented in this volume were carefully reviewed and selected from 42 initial submissions.